MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI METODE DEMONSTRASI - Siti Suwaibatul Aslamiyah (Universitas Islam Lamongan, 2018)
Abstract: Educator is one component in education that has an important role. Given the importance of the presence of an educator in front of students, Educators are required to master various learning methods, one of which is the demonstration method. The demonstration method is a teaching method where both educators and students together do something as a practical exercise from what they know. The demonstration method will provide a clear picture and concrete understanding of a process or skill in learning concepts rather than just hearing, explaining or just verbal statements from educators. The use of demonstration method provides many benefits including; making teaching clearer and more concrete, focusing the attention of students, more directing the learning process of students on the material being studied, more attaching experience and impressions as learning outcomes to students, making students easier to understand what is learned, making the teaching process more interesting, stimulating students to actively observe and adjust between theory and reality, helping students understand clearly the course of a process of an object, and facilitating various types of explanations. Thus, the use of demonstration method can broadly increase students 'motivation to learn, if students' learning motivation increases, eventually learning objectives can be achieved.